Syndrome de Treacher - Collins: Prise en charge bucco-dentaire d'un cas pediatrique - Nada CHEDID; Pascale ABOU RJEILY (International Arab Journal of Dentistry (IAJD), 2020)
Treacher Collins syndrome (TCS), also called Franceschetti syndrome, is a congenital malformation of the face, with associated dental pathologies such as dental hypoplasia, dental agenesis, tooth eruption and position anomalies as well as multiple caries lesions. Considering that the dentist plays an essential part in the multidisciplinary health rehabilitation of patients with TCS, the purpose of the present paper is to describe the dental management of a child presenting with TCS.